TYROSINASE INHIBITORS FROM HALOPHILIC AND MARINE-DERIVED FUNGI: ACTIVE METABOLITES, INHIBITORY ACTIVITIES, AND POTENTIAL APPLICATIONS IN HYPERPIGMENTATION - Maurayanti, Putu Ristanaya; Nursid, Muhammad; Dewi, Luh Putu Mirah Kusuma; Samirana, Putu Oka (LPPM STIKES BULELENG, 2026)
Skin hyperpigmentation is a dermatological problem associated with increased melanin production, in which tyrosinase plays an important role in melanogenesis. Halophilic and marine-derived fungi can adapt to extreme environmental conditions and may produce secondary metabolites with biological activities, including tyrosinase inhibition. This review aimed to evaluate the potential of halophilic and marine-derived fungi as sources of tyrosinase inhibitors by examining fungal origin, species, sample type, active metabolites, assay methods, and reported inhibitory activity. A literature search was conducted using Google Scholar with keywords related to marine fungi, endophytic fungi, halophilic fungi, and tyrosinase. Original research articles published in English that reported tyrosinase inhibitory activity of halophilic or marine-derived endophytic fungi were considered. Eleven articles were selected for further analysis. The findings showed that fungi associated with sponges, algae, sediments, and marine environments produced metabolites with varying tyrosinase inhibitory activities. Several isolated compounds exhibited strong activity, with lower IC50 values than kojic acid, whereas crude extracts generally showed lower activity. Azaphilone, polyketide, and related metabolites were reported among several active isolates. However, most studies were limited to in vitro enzyme assays, with insufficient validation of mechanisms, toxicity, and efficacy in cellular or in vivo models. Halophilic and marine-derived fungi have potential as sources of novel tyrosinase inhibitors, but standardized assays, mechanistic characterization, and safety and efficacy validation are needed to support further development as potential skin-lightening agents.